Karakteristik Kimia Tepung Umbi Talas (Colocasia esculenta) Kultivar Tanimbar dengan Lama Fermentasi - Siletty, Lambertina; Polnaya, Febby J; Moniharapon, Erynola (Universitas Pattimura, 2022)
Tanimbar taro flour is a processed product from tubers originating from Tanimbar, West Southeast Maluku, and is known as “tarro pici” and has not been widely researched regarding the fermentation treatment. Fermentation was carried out to change the properties of Tanimbar taro flour. This study aimed to characterize the chemical properties of taro flour fermented using 0.5% yeast fermipan. Fermentation was carried out for 0 hours (control), 24, 48, and 72 hours in a closed container. The analysis carried out includes water content, ash content, the fat content of the Soxhlet method, Kjeldahl micro protein content, fiber content, and carbohydrate content (by diff.). A non-factorial completely randomized design was used in this study and each treatment was repeated three times. The results showed that the water content, ash content, protein content, fat content, carbohydrate content (by diff.), and fiber content had a very significant effect on tanimbar taro flour. The best treatment was the 72-hour fermentation treatment to produce tanimbar taro flour with a moisture content of 8.61%, ash content of 0.50%, protein content of 5.12%, fat content of 1.02%, carbohydrate content of 84.76% and fiber content of 2.29%. Keywords: Fermentation; modification flour; Tanimbar taro bulb ABSTRAK Tepung umbi talas Tanimbar merupakan hasil olahan dari umbi yang berasal Tanimbar, Maluku Tenggara Barat dan dikenal dengan nama “kaladi pici” dan belum banyak diteliti terkait dengan perlakuan fermentasi. Fermentasi dilakukan untuk mengubah sifat-sifat tepung talas Tanimbar. Penelitian ini bertujuan untuk untuk mengkarakteristik sifat-sifat kimia tepung talas kultivas Tanimbar yang difermentasi menggunakan ragi fermipan sebanyak 0,5%. Fermentasi dilakukan selama 0 jam (kontrol), 24, 48, dan 72 jam dalam wadah yang tertutup. Analisis yang dilakukan meliputi kadar air, kadar abu, kadar lemak metode Soxhlet, kadar protein mikro Kjedahl, kadar serat, kadar karbohidrat (by diff.). Rancangan acak lengkap non-faktorial digunakan dalam penelitian ini dan setiap perlakuan diulang tiga kali. Lama fermantasi berpengaruh sangat nyata terhadap setiap parameter tepung talas tanimbar yang dianalisis. Perlakuan terbaik adalah perlakuan fermentasi 72 jam menghasilkan tepung talas tanimbar dengan kadar air 8,61%, kadar abu 0,50%, kadar protein 5,12%, kadar lemak 1,02%, kadar karbohidrat 84,76% dan kadar serat 2,29%. Kata kunci: Fermentasi; talas Tanimbar; tepung modifikasi